Propuesta de responsabilidad social empresarial como estrategia gerencial y administrativa de la mediana empresa del sector industrial en la ciudad de Tunja (Boyacá). (2020)
The proposal of Corporate Social Responsibility as a managerial and administrative strategy of the medium-sized company in the industrial sector in the city of Tunja, arises as a need that all national, regional and local organizations have been having to define mechanisms around the subject, according to the specifications and requirements defined by the State and others of international order, facing the field of action of the companies. This implies that evaluation parameters are necessarily established in environmental, safety and health at work as quality, understanding that companies must demonstrate results based on CSR in order to be consistent with the need to contribute to efficient development and timely from the region and the country. In this way, the current situation of the CSR processes in the medium-sized Company of the Industrial Sector of the City of Tunja is diagnosed from a Management and Administrative point of view, consulting and documenting the regulations applicable to the subject in the sector, presenting a proposal managerial and administrative that provides answers to the concerns and limitations of the current development of medium-sized industrial companies. Currently, CSR processes in the world, as in Colombia, have defined a new way of managing and administering an organization, especially because it allows for greater knowledge of its structure and, based on it, proposing alternatives that allow a redefinition of policies and actions in environmental, labor and quality matters, understanding the importance that they have in the competitiveness, productivity and profitability of companies.